Utility of the CPS + EG scoring system in triple-negative breast cancer treated with neoadjuvant chemotherapy. (August 2021) - Marmé, Frederik; Solbach, Christine; Michel, Laura; Schneeweiss, Andreas; Blohmer, Jens-Uwe; Huober, Jens; Fasching, Peter A.; Jackisch, Christian; Nekljudova, Valentina; Link, Theresa; Rhiem, Kerstin; Rey, Julia; et al.
Abstract: Background: Pathological complete response (pCR) after neoadjuvant chemotherapy (NACT) is associated with superior survival. This association is strongest in triple-negative breast cancer (TNBC). The CPS + EG system, based on pre-treatment clinical (C S) and post-treatment pathological stage (PS ), oestrogen-receptor status (E ) and grade (G ), leads to a refined estimate of prognosis after NACT in all-comers and hormone receptor–positive/human epidermal growth factor receptor 2 (HER2)-negative breast cancer. Here, we investigate if CPS + EG scoring provides a superior estimate of prognosis in TNBC to select patients for postneoadjuvant therapy. Methods: We calculated the CPS + EG score for 1795 patients with TNBC from 8 prospective German trials. Five-year disease-free survival (DFS) and overall survival estimates were calculated using the Kaplan-Meier method. Results: In TNBC, patients with pCR (ypT0/is ypN0, n = 822, 45.8%) had a 5-year DFS of 86%, whereas patients with residual American Joint Committee on Cancer stage I disease (n = 383; 21.3%) had a 5-year DFS of 77.5%.CPS + EG led to superior prognostic information compared with that provided by the clinical stage, but it was inferior to the prognostic information provided by the pathological stage (c-index statistics, p < 0.001). CPS + EG did not discriminate prognosis within the two best prognostic groups (score 1 and 2; n = 362; 37.2%). In contrast, pCR status added prognostic information beyond CPS + EG. Patients with a CPS + EG score of 3 had a 5-year DFS rate of 64% overall, but those with pCR had a 5-year DFS rate of 84%, and those without pCR had a 5-year DFS rate of only 49.7%. Conclusions: In TNBC, CPS + EG scoring provided inferior prognostic information compared with the pathological stage and was unable to identify patients without pCR and with a sufficiently good prognosis, who could avoid postneoadjuvant therapy. pCR remains the strongest and most clinically useful prognostic factor after NACT. Other biologic factors beyond pCR are needed in TNBC. Highlights: Clinical utility of CPS + EG in triple-negative breast cancer (TNBC) was assessed. 1795 patients with TNBC from 8 prospective neoadjuvant trials were anaylsed. CPS + EG does not add clinically useful information beyond the pathological stage. Pathological complete response remains the single most clinically useful prognostic factor after neoadjuvant chemotherapy.